Physiognomy of War: Ruins of Memory in Michael Ondaatje’s Anil’s Ghost - Yang, Lichung (Studies in Canadian Literature, 2015)
This essay explores how Michael Ondaatje’s thematic and formal treatment of the political violence in Anil’s Ghost can be illuminated with Walter Benjamin’s reflections on history as piles of debris. It argues that Ondaatje’s novel stands as, to adapt Benjamin’s phrase, an “allegorical way of seeing” into a war, which discloses itself through a variety of arresting images of ruins wrought by human violence on a vast scale. Teasing out the images of ruins in Ondaatje’s novel – from remnants, material debris, ruined landscape to scarred, wounded bodies, and the social ruination of the people’s lives – enables the reader to appreciate the way in which his famously fragmentary and ambivalent narrative inscribes the long- and short-term processes of political violence that leave their traces in types of ruins. The essay also suggests that Ondaatje’s fictional endeavor extends the materialist view of ruins to mark the trace of the ruinous experiences of war, given the nuance of the ruins he summons to mind. When staging the images of ruins, Ondaatje not only turns to architectural, corporal ruins, but also redirects his melancholy gaze toward the continuing war, toward vulnerable, neglected lives, and, in particular, the unspoken bonds formed between ordinary people.